Analysis on Teacher’s Social Action in Implementing Character Education to Digital Native Student in Surakarta City - Astutik, Dwi; Liestyasari, Siany Indria; Budiati, Atik Catur; Parahita, Bagas Narendra; Ghufronudin, Ghufronudin; Siregar, Riyadi Syafutra (Jurnal Pendidikan Progresif, 2025)
Abstract: Analysis on Teachers' Social Actions in Implementing Character Education to Digital Native Student in Surakarta City. Teacher’s Social Action in Implementing Character Education to Digital Native Student in Surakarta City. Objective of Research: This research aims (1) to identify the teacher’s attempt of inculcating character values to the Digital Native students having been exposed to information flow and technology, and (2) to analyze various attempts taken by teachers to inculcate the character values through Max Weber’s rational action perspective. Method: Through research method using qualitative study, the author dug data through in-depth interview and observation on the teachers’ attempt of particularly implementing character education at school. In addition, through learning process, the Project of Strengthening the Pancasila Student Profile can be chosen as a medium to inculcate the characters of Pancasila Student Profile inside the Digital Native students. Finding: The result of research mentions that the attempt taken by the teachers in inculcating character education is through learning process and beyond learning process. Beyond the learning process, the inculcation of character values is carried out through utilizing the Project of Strengthening Pancasila Student Profile. Conclusion: Every teacher’s action in inculcating the character values contains rationality, goal, and consideration in choosing the method. The most prominent consideration is based on the educator’s rationality to accommodate the rapid development of Digital Native students.  Keywords: digital native, character education, rational action, max weber.